(untitled) (Biological Sciences - PJSIR, 1999)
TheratesofhydrolysisofN-N’ -salicylidene-ethylenediamine(Hjsalen), havebeeninvestigatedinthepHrange 1.50-11.30 at 25°C in aqueous media containing 7% V methanol. Itwas observed thattherates of hydrolysis weredependent on pH values more basic than pH9.20.The rate-limiting stepin suchmedia wassuggested tobe:theattack ofhydroxide ions on theH2salen asaketo-form. The pH-independent reactions occuredatpHregion9.20-6.35. AtpHvalues moreacidic than 6.50, the hydrolysis rates became pH-dependent again and were correlated with the conversion of the substrate to its conjugateacid.Undertheseconditionsthepredominantreactionwasattackofwatermoleculesontheproton tedsubstrate. Furthermore, effects of certain transition metalions vizCe(IV), Ce(III), Cu(II) andZn(II) on thehydrolysis reaction rate havebeenexamined and interpreted onthebasisofformationoftricyclicchelate rings.Thermodynamic parameters have been also determined anddiscussed.